A theory of expert leadership - Amanda H. Goodall (Institute for the Study of Labor (IZA), 2012)
How much knowledge should leaders have of their organization's core business? This is an important question but not one that has been addressed in the management literature. In a new 'theory of expert leadership' (TEL), this paper blends conceptual work with recent empirical evidence. It suggests that organizations perform more effectively when led by individuals who have a deep understanding of the core business of their organization. Being a capable general manager is not sufficient. Expert leaders are those with (1) inherent knowledge, acquired through technical expertise combined with high ability in the core-business activity; (2) industry experience, which stems from time and practice within the core-business industry; and (3) leadership capabilities, which include management skills and a leader's innate characteristics. This paper criticizes the rise of the professional manager and generalist CEO. It argues that expert leaders improve organizational performance through knowledge-based strategy, by acting as a standard bearer, by creating the right environment for core workers, and, finally, by adopting the long view. The paper concludes by identifying the potential boundaries of TEL.
urn:nbn:de:101:1-201301213282
Keywords: J24; M12; M51; 330; expert leaders; CEOs; inherent knowledge; core business; organizational performance; Führungskräfte; Sachverständige; Führungsstil; Wissen; Kernkompetenz; Management; Unternehmenserfolg